The Effect of Green Accounting and Environmental Performance on The Value of Companies Moderated by Proptability in Idx30 Companies in 2018-2023 - Fitria, Yanisa Zahra Nurul; Novi Nurcahyani (Fakultas Ekonomi Universitas Garut, 2024)
This study addresses ongoing environmental issues, particularly in the manufacturing and mining sectors, which significantly contribute to environmental degradation. The research aims to understand the impact of green accounting and environmental performance on firm value, with profitability as a moderating variable. This is a quantitative study, utilizing a non-probability sampling method with purposive sampling techniques. The analysis methods used include classical assumption tests, determination coefficients, Moderate Regression Analysis, and hypothesis testing. The results of the study conclude that green accounting and profitability as moderating variables do not have an impact on firm value. In contrast, environmental performance and profitability as moderating variables do influence firm value. The simultaneous analysis shows that green accounting and environmental performance together affect firm value when moderated by profitability. The findings of this research are expected to raise awareness among business practitioners about the importance of considering environmental issues and the impact of environmental pollution caused by production processes, with an emphasis on planning through the concept of green accounting. This study focuses on the analysis of green accounting and environmental performance on firm value, moderated by profitability, in companies listed in the IDX30 index.